Research on Fabric Surface Effect Techniques to Design Men’s Garments for Sustainable Development - Le, Khanh Trang; Vu, Thi Phuong Thao (JST: Engineering And Technology For Sustainable Development, 2022)
Along with the development of industrialization and modernization, the rapid development of fast fashion has made the source of raw materials exhausted by the continuous purchasing and production in order to promptly meet the needs of customers. In addition, the emissions from the garment industry as well as the huge amount of discarded clothes that cannot be decomposed in time cause serious pollution. In the context that the world environment is at an alarming rate, the production of fashion products following sustainable fashion trends is a method of special interest. Sustainable fashion is being researched and applied more and more in the field of fashion design. In this article, the research team explores the sustainable fashion development orientation of companies and groups in the world and analyzes the development situation of sustainable fashion trends in Vietnam. The main method of research is using Boro and Sashiko techniques. This is one of the techniques that does not waste materials and creates interesting surface effects from the stitching technique. The research results are a combination of synthetic materials and recycled denim and stitching techniques to design a sustainable fashion collection. The study contributes to the development of a sustainable fashion product line serving the needs of society shortly, creating a new process that minimizes waste and harmful substances to the environment in the future.